PENGARUH KOMPETENSI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA KOPERASI UNIT DESA PEDUNGAN DENPASAR - Ni Kadek Mery Widiastuti; I Gusti Ngurah Eka Teja Kusuma; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Human resource management is part of organizational management that focuses on the element of human resources. The appropriate competence causes human resources to have superior performance, so as to encourage organizational success. The organization will develop and be able to survive if it is supported by employees who are competent in their respective fields. Meanwhile, Transformational Leadership is a leader who can motivate his followers to carry out above expectations and beyond self-interest for the benefit of the organization. . This study aims to test and obtain empirical evidence of the effect of competence and transformational leadership on employee performance at the Pedungan Village Cooperative Unit, Denpasar. The population in this study were all employees at the Pedungan Village Cooperative Unit, Denpasar as many as 37 employees. In this study, the sample of the entire population was 37 employees. The results showed that competence and transformational leadership had a positive and significant effect on employee performance